Could BCG be used to protect against COVID-19? - Redelman-Sidi, Gil (Nat Rev Urol, 2020)
Nearly 100 years since it was first used in humans as a vaccine for tuberculosis, Bacillus Calmette–Guérin (BCG) has been suggested as a possible agent to prevent coronavirus disease 2019 (COVID-19). A number of studies are underway to investigate this possibility but — even if they prove effective — many questions will remain.